2014
DOI: 10.3109/10428194.2013.878934
|View full text |Cite
|
Sign up to set email alerts
|

Initial transfusion intensity predicts survival in myelodysplastic syndrome

Abstract: We evaluated 52 patients with myelodysplastic syndrome (MDS) who had received at least one red blood cell (RBC) transfusion. In the 4-week period following the first transfusion, 24 patients (group 1) required no transfusion, while 28 (group 2) required transfusion of two or more units of RBCs. Survival was greater in group 1 (440 weeks vs. 167 weeks, p < 0.01), even when only international prognostic scoring system (IPSS) low and intermediate-1 risk patients were analyzed (median overall survival 491 vs. 170 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Benton et al 31 "history of RBC transfusion [was] significantly associated with inferior survival" Cakar et al 40 "no significant relationship was demonstrated between transfusion dependency and disease progression" Cermak et al 41 "Our results confirm a significant negative impact of transfusion dependency on survival in patients with early MDS without excess of blasts" Chan et al 42 "The intensity of transfusion required in the first few weeks after the first transfusion predicts disease severity and correlates with survival." Chee et al 43 "survival was not affected by the total number of RBC transfusions received (…) the results of the current study also suggest limited morbidity from iron overload in patients with RARS."…”
Section: Survivalmentioning
confidence: 66%
See 3 more Smart Citations
“…Benton et al 31 "history of RBC transfusion [was] significantly associated with inferior survival" Cakar et al 40 "no significant relationship was demonstrated between transfusion dependency and disease progression" Cermak et al 41 "Our results confirm a significant negative impact of transfusion dependency on survival in patients with early MDS without excess of blasts" Chan et al 42 "The intensity of transfusion required in the first few weeks after the first transfusion predicts disease severity and correlates with survival." Chee et al 43 "survival was not affected by the total number of RBC transfusions received (…) the results of the current study also suggest limited morbidity from iron overload in patients with RARS."…”
Section: Survivalmentioning
confidence: 66%
“…Fourteen studies reported data on survival following diagnosis of MDS in relation to transfusion frequency, dependency and/or cumulative burden. 8,14,15,18,26,[29][30][31][40][41][42][43][44][45] The majority reported an inverse relationship between RBC transfusion and survival. Seven studies demonstrated poorer overall survival associated with transfusion dependency 8,14,15,18,26,31,41 and four reported that greater transfusion intensity was associated with decreased overall survival 29,30,42 and/or leukaemia-free survival.…”
Section: Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…Although patients also suffer from an increased risk of infection or hemorrhage and may even progress to acute myeloid leukemia (AML), anemia is the most common form of cytopenia in MDS [2]. To overcome anemia, patients with MDS require chronic RBC transfusions [3], often resulting in iron overload [4,5], which is reflected by high serum ferritin (SF) levels.…”
Section: Introductionmentioning
confidence: 99%